A method of evaluating economic risk for an offshore field development project - 443804 Abdul Rahman Mohamed (Kuala Lumpur : Universiti Teknologi Malaysia, 1984)
Thesis (Bachelor of Petroleum and Natural Gas Engineering) - Universiti Teknologi Malaysia, 1984